Quality Improvement Initiative for Assessing Allografts after Lung Transplantation. Issue 2 (March 2019) - Hayes, Don; Nicholson, Kerri L.; Miller, Rebecca; Nance, Ashley E.; Kirkby, Stephen E.; Parker, William; Baker, Peter B.
Abstract : Introduction: The histologic evaluation of lung allografts after transbronchial biopsy (TBBx) is a key component of the clinical care of lung transplant recipients. With established guidelines on diagnosing allograft rejection, no specific recommendations exist on timeliness to reaching a diagnosis and initiating therapy. A quality improvement initiative focused on 3 key stages of achieving a prompt diagnosis of acute cellular rejection including tissue processing, interpretation, and notification to the treating transplant pulmonologist was initiated to minimize time to treatment onset. Methods: We completed a single-center cohort study on all surveillance and clinically indicated TBBx from September 2006 to March 2018. The rapid tissue processing, interpretation, and notification system was instituted in March 2011 with data before this date serving as baseline. Results: We enrolled 28 patients who underwent 210 TBBx (1 excluded due to unknown notification date). Thirty-eight TBBx were included at baseline before implementation of the rapid tissue processing and communication system; 171 were included after implementation. Median time to notification following the change was 0 days (interquartile range, 0–1) compared with 1 day (interquartile range, 1–1) before the change ( P < 0.001). After the change, same-day notification increased, with 110 (64%) TBBx resulting in same-day notification compared with 0 before ( P < 0.001). We initiated treatment of acute cellular rejection on the day of diagnosis for the entire cohort. Conclusions: This quality improvement initiative resulted in more efficient analysis of TBBx of allografts in lung transplant recipients and faster communication of results to the clinical team.